Enquadramento contabilístico e fiscal das empresas em Portugal, Reino Unido e EUA: um estudo comparativo - Castro, Filipa Lascasas de (2022)
This dissertation intends to develop an accounting and fiscal framework for companies residing in three different socio-economic contexts, having as a model Portugal, United Kingdom and United States of America (USA), starting with a historical contextualization of the three countries followed by a comparative analysis of the different accounting systems adopted by them - the Normas Contabilíticas de Relato Financeiro (NCRF) in the case of Portugal, the International Financial Accounting Standards (IFRS) in the case of the United Kingdom and the United State General Accepted Accounting Principles (US GAAP) in the case of the USA – including the tax impact of the Código do Imposto sobre o Rendimento das Pessoas Coletivas (CIRC) in the part corresponding to Portugal. Thus, the impact of the adoption of different accounting standardization systems by each of the countries under analysis is evaluated, together with their fiscal constraints on the tax burden of companies, seeking to understand the position of countries in the accounting standardization process and how is that these differences can impact users of financial statements in their interpretations and decision-making. Thus, supported by a methodological approach of document analysis of NCRF, IFRS and US GAAP, six practical cases are developed that portray the accounting and tax treatment of inventories, tangible fixed assets, intangible assets, investment properties, customer impairment losses and leases . With the development of this dissertation, it is intended to prove that the three countries are in different positions with regard to their tax and accounting systems, giving rise to different taxation and reporting of financial information under identical circumstances. This also leads to the conclusion that the diversity of information reveals that perfect accounting harmonization has not yet been achieved and that the concrete formula for how to convey a true, reliable and transparent view of a company's financial position and performance is not yet fully defined. that allows users of financial statements to make fully aware decisions, since, depending on the context in which they are calculated, there are different statements for the same cases.